2014
DOI: 10.1007/s12035-013-8630-4
|View full text |Cite
|
Sign up to set email alerts
|

PAS Kinase Is a Nutrient and Energy Sensor in Hypothalamic Areas Required for the Normal Function of AMPK and mTOR/S6K1

Abstract: The complications caused by overweight, obesity and type 2 diabetes are one of the main problems that increase morbidity and mortality in developed countries. Hypothalamic metabolic sensors play an important role in the control of feeding and energy homeostasis. PAS kinase (PASK) is a nutrient sensor proposed as a regulator of glucose metabolism and cellular energy. The role of PASK might be similar to other known metabolic sensors, such as AMP-activated protein kinase (AMPK) and the mammalian target of rapamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 50 publications
(75 reference statements)
1
42
0
Order By: Relevance
“…In addition, the mammalian ortholog of fray is a Ste20-like kinase (PASK; Leiserson et al 2000, 2011), which has a role as a metabolic sensor that is required for energy balance in mice (Hao et al 2007). Importantly, the energy-sensing role of PASK has been shown to be essential for the normal function of AMPK and mTOR/S6K1 (Hurtado-Carneiro et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mammalian ortholog of fray is a Ste20-like kinase (PASK; Leiserson et al 2000, 2011), which has a role as a metabolic sensor that is required for energy balance in mice (Hao et al 2007). Importantly, the energy-sensing role of PASK has been shown to be essential for the normal function of AMPK and mTOR/S6K1 (Hurtado-Carneiro et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…In support of this progrowth association, PAS kinase overexpression suppresses a temperature-sensitive mutation of TOR2 in yeast ( tor2ts ; Cardon et al ., 2012 ). In addition, PAS kinase was recently shown to be required for proper activation of AMPK and mTOR in the hypothalamus, where AMPK activation by nutrient depletion and TORC1 activation by refeeding are both blunted in PASK − / − mice ( Hurtado-Carneiro et al ., 2013 , 2014 ). The converse association is found in yeast, in which AMPK/SNF1 is required for the activation of PAS kinase by non­glucose carbon sources ( Grose et al ., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the present findings. Other studies in mammals reported that PSK kinase deficiency is associated with relative decrease in insulin production, insulin resistance, triglyceride accumulation, and protects against high fat‐diet‐induced obesity (Cardon & Rutter, ; Hao et al, ; Hurtado‐Carneiro et al, ; Pape et al, ). Our results do not only provide an insight into the mechanism of biological rhythms but are also potentially useful for the design of new treatments for human metabolic syndrome and/or diabetes.…”
Section: Discussionmentioning
confidence: 99%